The effects of a bonus tax on manager compensation and welfare - Doina Maria Radulescu (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper analyses the implications of a currently publicly debated issue, namely the introduction of a bonus tax. We shed light on the effects of the bonus tax on compensation components and study its incidence. We use the Principal Agent model within a two-country framework and consider two main scenarios. In the first scenario the firm cannot relocate managers between countries whereas in the second scenario relocation possibilities exist. Our findings show that the effort based compensation component always rises in the country introducing the tax such that the optimal contracts are tilted towards more effort based pay. Moreover, the bonus tax negatively affects profits and dividends and thus the incidence falls on the firm's shareholders. With no relocation possibilities, the country that does not introduce such a tax will be worse off in terms of welfare, as the dividend income accruing to its residents declines. Accordingly, the bonus tax can be interpreted as a transfer from the worldwide shareholders to the government levying the tax. However, the welfare results may be reversed when manager relocation is an alternative. In this case, welfare in the country introducing the tax is lower than in the no relocation scenario, while the country that does not levy a bonus tax might even gain in welfare terms.
Keywords: H24; H22; J22; J30; 330; bonus tax; labor taxation; effort; manager compensation; welfare; Erfolgsbeteiligung; Leistungsorientierte Vergütung; Führungskräfte; Lohnsteuer; Steuerwirkung; Wohlfahrtseffekt; Agency Theory; Zwei-Länder-Modell; Arbeitsmobilität; Theorie